(untitled) (Altre Modernità, 2019)
The following paper describes the main aspects of accessible tourism discourse by analysing some specific textual typologies and related translations (ENGITA- ENG) dedicated to the promotion of accessible tourism services, attractions and sites. Accessible tourism can be defined as a form of tourism that “enables people with access requirements, including mobility, vision, hearing and cognitive dimensions of access, to function independently and with equity and dignity through the delivery of universally designed tourism products, services and environments” (Darcy and Dickson 34). Despite the increasing awareness on the economic assets and ethical implications of this sector, literature in the field generally ignores the linguistic features characterising accessible tourism discourse, thus somehow adding a further, intangible barrier to the physical and architectonical obstacles upon which the leading tourism industry seems to be mainly concerned about. The aim of this research is to identify linguistic, translational and contextual features that may boost – or sometimes hinder – the ‘real accessibility’ of accessible tourism discourse in terms of textual contents, contextual characteristics, cultural and inclusive functions of its promotional materials, in order to provide some useful considerations on the need to question the curren linguistic representation of disability and develop a more inclusive approach in tourist promotional texts.